INFRINGEMENT OF TRADEMARK: A GROWING CONCERN (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Due to the negative impact on both brand equity and bottom lines, trademark infringement has emerged as a significant issue for businesses throughout the world. Robust trademark protection via legislative enforcement is vital in light of shifting economic practices and globalization. Both companies and people are becoming more worried about trademark infringement because of the damage it may do to a company's image and bottom line. Trademark protection via the enforcement of trademark laws is now more critical than ever in light of changes in trade and commercial activities as well as globalization. In this in-depth post, we will look at trademark infringement from every angle: the legal framework, landmark cases, and remedies that rights holders have at their disposal.